The Impact of Elective Colon Resection on Rates of Emergency Surgery for Diverticulitis - Simianu, Vlad V (Ann Surg, 2016)
OBJECTIVE: To determine the impact of elective colectomy on emergency diverticulitis surgery at the population level. SUMMARY BACKGROUND DATA: Current recommendations suggest avoiding elective colon resection for uncomplicated diverticulitis because of uncertain effectiveness at reducing recurrence and emergency surgery. The influence of these recommendations on use of elective colectomy or rates of emergency surgery remains undetermined. METHODS: A retrospective cohort study using a statewide hospital discharge database identified all patients admitted for diverticulitis in Washington State (1987–2012). Sex and age-adjusted rates (standardized to the 2000 state census) of admissions, elective and emergency/urgent surgical and percutaneous interventions for diverticulitis were calculated and temporal changes assessed. RESULTS: 84,313 patients (mean age 63.3 years and 58.9% female) were hospitalized for diverticulitis (72.2% emergent/urgent). Elective colectomy increased from 7.9 to 17.2/100,000 people (p<0.001), rising fastest since 2000. Emergency/urgent colectomy increased from 7.1 to 10.2 per 100,000 (p<0.001), non-elective percutaneous interventions increased from 0.1 to 3.7 per 100,000 (p=0.04) and the frequency of emergency/urgent admissions (with or without a resection) increased from 34.0 to 85.0 per 100,000 (p<0.001). In 2012, 47.5% of elective resections were performed laparoscopically compared to 17.5% in 2008 (when the code was introduced). CONCLUSIONS: The elective colectomy rate for diverticulitis more than doubled, without a decrease in emergency surgery, percutaneous interventions or admissions for diverticulitis. This may reflect changes in thresholds for elective surgery and/or an increase in the frequency or severity of the disease. These trends do not support the practice of elective colectomy to prevent emergency surgery.